Cultivation and Growth Dynamics of Capelin (Mallotus villosus) from Hatch to Adulthood - Tómas Árnason; Birkir Bárðarson; Agnar Steinarsson (Fishes)
This study describes the first successful rearing of capelin from hatch to adulthood in a laboratory setting using intensive culture methods. Over the span of about two years, the capelin were reared in aquaculture tanks under a constant temperature of 7 °C. The capelin demonstrated a robust linear growth during their first year of life, with a mean length increment of 0.36 mm per day. Due to their accelerated growth, some of the capelin became sexually mature as early as one year post-hatch. The first year was characterized by a rapid increase in condition factor (CF) while the second year showed a plateau. The von Bertalanffy growth equation effectively described the two-year growth of the cultivated capelin, predicting an asymptotic length (L∞) of 18.4 cm, similar to the 18.6 cm median L∞ of wild Icelandic capelin (1981–2018 cohorts). The cultivated capelin were projected to reach this length in 2.6 years, compared to about 6 years for wild capelin. This study provides new insights into the growth dynamics of capelin and although the species is sensitive to handling, it demonstrates that intensive culture methods can be used to investigate biological aspects of this important forage species.